PENGEMBANGAN LEMBAR KERJA (LKS) BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI HIMPUNAN SISWA KELAS VII SMP N 10 MUARA BUNGO - Khairul Nisa; Buyung Buyung; Silvia Fitriani (PHI: Jurnal Pendidikan Matematika, 2018)
Abstract : This study aims to develop LKS based Problem Based Learning (LKS) on the set material. In addition, also see the quality of LKS developed viewed from aspects of validity, practicality and effectiveness. This type of research is research development or Research and Development (R&D). This study follows the steps of the ADDIE development model covering five stages of development: analysis, develompment, implementation and evaluation. The subject of this research is the students of class VII A SMPN 10 Muara Bungo. Research instruments on this development are questionnaires and questions. The questionnaire consisted of a validation sheet by 3 experts, materials experts, design experts, and media experts as well as individualized questionnaires, small group trials and field trials. While the instrument in the form of questions consists of a matter of pre-test and post-test. After the LKS was developed, the LKS was validated by 3 validators. The percentage of results obtained after validation is: for the material expert's assessment of 81.8% with the category "very valid", the design expert of 77.8% with the category "valid" and 87.7% media experts with the category "very valid. Then the LKS in the test try, the percentage of test results obtained are: individual test of 82.5% with the category of "very practical", small group testing of 89.7% with the category "very practical" and field trials of 83,7% with very practical category. Furthermore, to assess the effectiveness of LKS seen from the results of pre-test and post-test conducted by students, then calculated using the calculation of t-test statistics, obtained tcount of 9.24 and ttable of 2.03, because tcount larger ttable it can be concluded that the LKS developed effectively. Based on the description above, the result of research of development of LKS based on PBL is categorized as valid, practical, and effective.Keywords: Student Worksheet (LKS), Problem Based Learning (PBL), ADDIE Development Model